#1**+1 **

Any radicals multiplied by each other can be simplified. Just combine them into one radical.

\(\sqrt{2}*\sqrt{7}*\sqrt{13}=\sqrt{2*7*13}\)

From there it is just simple multiplication.

\(\sqrt{2*7*13}=\sqrt{14*13}=\sqrt{182}\)

So, your answer is √182.

AdamTaurus Jan 17, 2018

#1**+1 **

Best Answer

Any radicals multiplied by each other can be simplified. Just combine them into one radical.

\(\sqrt{2}*\sqrt{7}*\sqrt{13}=\sqrt{2*7*13}\)

From there it is just simple multiplication.

\(\sqrt{2*7*13}=\sqrt{14*13}=\sqrt{182}\)

So, your answer is √182.

AdamTaurus Jan 17, 2018